Pengaruh Endorsement Selebgram Terhadap Perilaku Konsumsi Produk Makanan Oleh Mahasiswa Jurusan Ilmu EKonomi Universitas Negeri Surabaya - Tasya Putri Zavida; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2021)
Consumption is an activity to buy and use goods and services to meet the needs of an individual. The consumption of each individual varies greatly. This is what is called consumption behavior. The diversity of consumption behavior causes more and more business actors to fulfill their needs, causing business competition. This makes business people have to rack their brains so that they are not less competitive with other business people. Marketing by utilizing digital technology and social media is one way. Through Instagram social media, marketing is carried out by users themselves who have a large number of followers (celebgrams). Marketing carried out by this program is in the form of endorsements. This research will discuss the effect of celebram endorsement on the consumption behavior of students majoring in economics, State University of Surabaya. The result of this research is that the endorsement by celebrams has a significant effect on the food product consumption behavior of students majoring in economics at the State University of Surabaya by 28.3%.